2022
DOI: 10.1002/ijgo.14498
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factor of postoperative adhesions following repeated cesarean section: A prospective cohort study

Abstract: Cesarean delivery is a commonly practiced obstetrical surgical intervention. 1 Its rate has risen worldwide, 1 reaching 52% in 2018 in Egypt. 2 This leads to increased repeat cesarean deliveries and related morbidity. 3 Intraperitoneal adhesions result from abdominal or pelvic surgeries. They have serious consequences such as intestinal obstruction, chronic pelvic pain, ectopic pregnancy, infertility, visceral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
(76 reference statements)
1
3
1
Order By: Relevance
“…Salim et al 23 also did not demonstrate an association between adhesion formation and the time interval between the CD, a period of time that may indicate the occurrence of vaginal births after CD. Our results are also not in agreement with Aboshama et al, 8 which demonstrated that a higher parity order was associated with adhesion formation. It should be noted that in these studies the sample size was small and may have lacked the statistical power to identify some predisposing factors.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Salim et al 23 also did not demonstrate an association between adhesion formation and the time interval between the CD, a period of time that may indicate the occurrence of vaginal births after CD. Our results are also not in agreement with Aboshama et al, 8 which demonstrated that a higher parity order was associated with adhesion formation. It should be noted that in these studies the sample size was small and may have lacked the statistical power to identify some predisposing factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Our study found that a maternal age of 35 years or older at the first CD was associated with an increased risk for adhesion formation. This association was also observed by Hesselman et al 21 and Aboshama et al 8 Conversely, Herzberger et al 22 and Salim et al 23 did not find any effect of age on PA formation. Aside from the lack of statistical power in these studies, the findings may also be related to the consideration of age as a continuous rather than a dichotomous variable.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations